Comparison of severe pneumonia caused by Human metapneumovirus and respiratory syncytial virus in hospitalized children - Yuqing Wang; Wei Ji; Zhengrong Chen; Yong Dong Yan; Xuejun Shao; Jun Xu (Indian Journal of Pathology and Microbiology, 2014)
Objectives: The objective of this study is to compare the incidence and clinical characteristics of severe pneumonia caused by Human metapneumovirus (hMPV) to respiratory syncytial virus (RSV) infection in children. Patients and Methods: A total of 151 children hospitalized with severe pneumonia, were tested for hMPV using reverse-transcription polymerase chain reaction. At the same time, samples were tested for RSV and other common respiratory viruses. Medical records, including clinical, laboratory data, and chest radiography findings, were reviewed for all children. Results: Of the 151 samples, 88 (58.3%) were positive for respiratory viruses. Of the 88 positive, there were 6 (4.0%) with hMPV, 66 (43.7%) with RSV, 13 (8.6%) with influenza A, 2 (1.3%) with parainfluenza virus III, 1 (0.7%) with parainfluenza virus I, 1 (0.7%) with adenovirus and 1 (0.7%) with influenza B. hMPV-infected patients were significantly older than RSV-infected patients (P < 0.001). Children with hMPV pneumonia had fever more frequently (P = 0.03). Two hMPV-positive patients (33.3%) required admission to an intensive care unit, and two patients (33.3%) required mechanical ventilation. The duration of illness was 18.33 ± 7.09 days. These characteristics of hMPV infections were similar to patients with RSV infections. Conclusion: Human metapneumovirus is an infrequent viral pathogen causing severe pneumonia in children. Children with hMPV were older than those with RSV. The disease caused by hMPV was similar in presentation and severity to RSV, with a minority of children requiring additional respiratory support.